Pengaruh Penggunaan Media Big Book Terhadap Kemampuan Berbicara Anak Usia 5-6 Tahun di PAUD Al-Hasanah Desa Marenu - Mawaddah Warohma Siregar; Humaidah Br. Hasibuan; Raisah Armayanti Nasution (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This research is an experiment with a pre-experimental design of the One Group Pretest-Posttest type. The total population involved in this research was 20 children. Problem formulation: How does the use of big book media improve the speaking skills of young children aged 5-6 years at PAUD Al-Hasanah Marenu? Does big book media have an influence on the speaking ability of children aged 5-6 years at PAUD Al-Hasanah Marenu? This research aims to: see how big book media influences the speaking abilities of young children at PAUD Al-Hasanah Marenu. To prove whether or not there is an influence from big book media on the speaking abilities of children aged 5-6 years at PAUD Al-Hasanah Marenu. The research method used is quantitative, so all data is analyzed numerically and statistically. The results of this research show that learning with big book media has a significant influence on the speaking abilities of children aged 5-6 years at PAUD Al-Hasanah Marenu. These results are proven by: Normality testing: pre-test data is 0.107 and post-test is 0.092, both of which are greater than 0.05, which means the data is normally distributed. Hypothesis calculation: the calculated t result of 20.466 is greater than the t table of 2.179 at the α = 0.05 level, so H0 is rejected and H1 is accepted. So, it can be concluded that the use of big book media has a significant effect on the speaking ability of children aged 5-6 years at Al-Hasanah PAUD Marenu Village.